Poaceae from Yanachaga-Chemillén National Park (Oxapampa, Pasco, Perú). Part I: Bambusoideae - La-Torre, María I. (2003)
This work is the first part of biodiversity study of Poaceae family from Yanachaga-Chemillen National Park and surroundings places (10º35´ − 10º10´ S and 75º10´ − 75º45´ W and from 300 to 3800 m). We analysed the material colected for us since 1995 to 1996 and material deposited in the Herbario San Marcos of Museo de Historia Natural and Missouri Botanical Garden. This first part is dedicated to the Bambusoideae biodiversity. A total of seven genera and 23 species have been registered. In the woody bamboos group, genus Chusquea was the mayor species number (seven). The genus Olyra is the most diverse of the herbaceous bamboos with five species. Descriptions of subfamily, genera and keys for genera and species are developed. Ecology, distribution and studied material are indicated.